The Impact Of Morals On Fatwas: An Applied Study Of The Fatwas Issued By Egypt’s Dar Al Iftaa - Hamza Abed AlKarim Hammad; Mahmoud Mohamed Ali Mahmoud Edris (Universiti Sains Islam Malaysia, 2026)
Morals constitute an important part of the components of the Islamic religion. Therefore, this paper aims to shed light on the importance of morals and their impact on the contemporary jurisprudential fatwas through the applied study of the fatwas issued by Egypt’s Dar Al Iftaa. This paper adopts the approach of content analysis and the objective examination of fatwas. The researcher concluded that there is an impact of morals in these fatwas, whether in terms of analysis of fatwa topics; Egypt’s Dar Al-Iftaa invested in noble morals to infer many modern matters that did not exist in the Islamic jurisprudential heritage, in addition to the type of jurisprudential rulings (obligatory, desirable, permissible, disliked, forbidden). This paper highlights the fact that morals are considered among the origins of rulings and fatwas in Islamic jurisprudence, and they can be relied upon to reach jurisprudential rulings and fatwas for emerging events such as modern economic and medical issues that need a definitive statement of jurisprudence. This study may be the first of its kind in terms of linking the impact of morals on contemporary fatwas through the applied study of the fatwas issued by Egypt’s Dar Al Iftaa. Thus, it opens the door for researchers to study the impact of morals on contemporary fatwas issued by the various fatwa houses.